Sericin Ser3 Ectopic Expressed in Posterior Silk Gland Affects Hemolymph Immune Melanization Response via Reducing Melanin Synthesis in Silkworm - Yongfeng Wang; Meijuan Shi; Jiameng Yang; Lu Ma; Xuedong Chen; Meng Xu; Ruji Peng; Guang Wang; Zhonghua Pan; Yanghu Sima; Shiqing Xu (Insects, 2023)
The transgenesis of silkworms is an important way to innovate genetic resources and silk function. However, the silk-gland (SG) of transgenic silkworms, which is the most concerned target tissue of sericulture, often suffers from low vitality, stunting and other problems, and the reasons are still unknown. This study trans engineered recombinant Ser3, a middle silk gland (MSG) specific expression gene, in the posterior silk gland (PSG) of the silkworm, and studied hemolymph immune melanization response changes in mutant pure line SER (Ser3+/+). The results showed that although the mutant had normal vitality, the melanin content and phenoloxidase (PO) activity in hemolymph related to humoral immunity were significantly reduced, and caused significantly slower blood melanization and weaker sterilization ability. The mechanism investigation showed that the mRNA levels and enzymatic activities of phenylalanine hydroxylase (PAH), tyrosine hydroxylase (TH) and dopamine decarboxylase (DDC) in the melanin synthesis pathway in mutant hemolymph, as well as the transcription levels of the PPAE, SP21 and serpins genes in the serine protease cascade were significantly affected. Moreover, the total antioxidant capacity, superoxide anion inhibition capacity and catalase (CAT) level related to the redox metabolic capacity of hemolymph were significantly increased, while the activities of superoxide dismutase (SOD) and glutathione reductase (GR), as well as the levels of hydrogen peroxide (H2O2) and glutathione (GSH), were significantly decreased. In conclusion, the anabolism of melanin in the hemolymph of PSG transgenic silkworm SER was inhibited, while the basic response level of oxidative stress was increased, and the hemolymph immune melanization response was decreased. The results will significantly improve the safe assessment and development of genetically modified organisms.